Tinjauan Hukum Islam Terhadap Praktik Sewa-Menyewa Kios (Studi Kasus Di Menco Raya, Kelurahan Gonilan, Kartasura) - Pratiwi, Ayuk; , Drs. Marpuji Ali, M.SI; , Nurul Huda, M.Ag (2016)
Tenancy is a form of action that is frequently carried out human muamalah to make ends meet. These needs may include goods or services that benefit does not have, such as renting out stalls for entrepreneurs. People who rent stalls for entrepreneurs. The rental kiosk in Menco Kingdom, Village Gonilan, Kartasura applying the advance payment was banned because it contains gharar. The aim of this study is to describe and explain the implementation of a cash advance kiosks in Menco Kingdom, Village Gonilan, Kartasura. And explain the views of Islamic law on the implementation of advance leasing (Ijarah) in kiosk Menco Kingdom. This research uses field research (field research) with descriptive qualitative approach. Source of data used primary data sources and secondary data sources. Data collection is done by observation, interview, documentation. Data were analyzed using qualitative methods or ways of thinking inductively. Based on the results of this study concluded that an advance payment in the rental kiosk in Menco highway is' urf or custom for the kiosk owner who rents a kiosk with payment systems per year. Lease contract carried stall stall stall owners and tenants in accordance with the pillars and the terms leasing (Ijarah), so that the law is valid. Practice advances in the rental kiosk done in three ways: first application of the system of advance payment does not come back at all, if the tenants fail rented stall, the second application of the system of advance payment will be returned to the conditional (finding a replacement or new tenants), the third application of the system advance payment will be returned to the contract / new deal. The application of advances should be done as long as no party feels aggrieved. Cash advance to avoid any breach of contract between the owner of the stall and stall tenants